A rare case of cervical abscess caused by Parvimonas micra. (June 2021) - Fujiwara, Erina; Tsuda, Takeshi; Wada, Kento; Waki, Sadanori; Hanada, Yukiko; Nishimura, Hiroshi
Cervical abscesses develop in the tissue spaces between the cervical fascia. The rapid expansion of these abscesses can lead to fatal outcomes. We describe a case of a deep cervical abscess caused by Parvimonas micra . He was referred to our department with complaints of sore throat and neck pain. Ultrasonography revealed a hypoechoic area in the cervical interfascicular space. An ultrasound-guided puncture was performed to collect pus for bacteriological examination. Subsequently, a contrast-enhanced computed tomography scan revealed a multi-focal abscess extending from the left mandible to the left side of the neck, without any mediastinal abscess. An emergency drainage and antibacterial therapies were performed, and the patient progressed well. Parvimonas micra, a gram-positive anaerobic bacterium, was detected in the pus collected before incision, and appropriate antibiotics were immediately administered. The collection of pus prior to incision and drainage aids accurate identification of the causative organism and appropriate treatment.